2019
DOI: 10.3389/fphar.2019.01189
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Decreases Mitochondria-Mediated Apoptosis and Autophagy Dysfunction in Hepatocytes of Experimental Autoimmune Hepatitis Model via the Akt/mTOR Signaling

Abstract: Autoimmune hepatitis (AIH) is characterized by massive immune cell-mediated hepatocyte destruction. Glucocorticoids, particularly methylprednisolone (MP), are the most effective treatment for AIH; however, the mechanism underlying the effects of glucocorticoid treatment has not been fully elucidated. The present study explored the effects of MP on damaged hepatocytes in mice with concanavalin A (ConA)−induced experimental autoimmune hepatitis (EAH). C57BL/6 mice were divided into three groups: a normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The EAH model was established at 12 h after an injection of ConA with a dose of 20 mg/kg through the tail vein, which was based on our previous study and other reported articles [11][12][13][14] . To evaluate the EAH model, the mice were divided into two groups: (1) Mice were given a single intravenous injection of normal saline as a vehicle control.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAH model was established at 12 h after an injection of ConA with a dose of 20 mg/kg through the tail vein, which was based on our previous study and other reported articles [11][12][13][14] . To evaluate the EAH model, the mice were divided into two groups: (1) Mice were given a single intravenous injection of normal saline as a vehicle control.…”
Section: Experimental Designmentioning
confidence: 99%
“…To investigate the role of cDCs in the pathogenesis of EAH, we developed a mouse model of ConA-induced AIH as in our previous study 11,14,19 . As shown by liver function and H&E, EAH was successfully established after ConA injection in EAH model ( Supplementary Fig.…”
Section: Circulating and Intrahepatic Mature Cdc Accumulation In Eahmentioning
confidence: 99%
“…Furthermore, it was evident that mTOR may affect diverse processes in T cells by coordinately regulating immune receptor signaling pathways, metabolic programs and migratory activity [45]. It has been reported that the mitochondria‐mediated apoptosis and autophagy dysfunction in Con A‐induced hepatocyte injury in vivo and in vitro were connected with the Akt/mTOR signaling pathway [46]. Apoptosis is considered as a crucial component of various processes, including development of the immune system, and inappropriate apoptosis (either too little or too much) is a vital factor in the generation of AIH.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced numbers of autophagosomes were present in the MP treated group compared to the conA group. It was further shown that MP attenuated the mitochondria-mediated autophagy and apoptosis[ 655 ]. In a second report on the same experimental model, accumulation of mature conventional dendritic cells (cDCs) was observed in the liver.…”
Section: Various Diseasesmentioning
confidence: 99%